Original paperAssociation of the rs1801133 variant in the MTHFR gene and sporadic Parkinson’s disease - García, Silvia; Coral-Vázquez, Ramón Mauricio; Gallegos-Arreola, Martha P.; Montes-Almanza, Luis Ángel; Canto, Patricia; García-Martínez, Froylan Arturo; Chavira-Hernández, Gerardo; Palma-Flores, Carlos; Dávila-Maldonado, Luis; Cuevas-García, Carlos F.; Hernández, Luz Berenice López (Folia Neuropathologica, 2015)
The MTHFR gene has been reported as a susceptibility locus for sporadic Parkinson’s disease (sPD). The functional variant rs1801133 has been linked to hyperhomocysteinemia and dopaminergic cell death. Among different populations, Mexican-Mestizos (most present-day Mexicans) have the highest frequency of this variant. Therefore, we sought to determine a possible association of rs1801133 with SPD. In total, 356 individuals were included: 140 patients with PD, diagnosed according to the Queen Square Brain Bank criteria, and 216 neurologically healthy controls. Genotyping was performed using TaqMan probes for rs1801133 and real-time PCR. Logistic regression analysis with adjustment for smoking and gender was used to test for an association between genotype and SPD. The CC genotype was associated with SPD; exp() = 2.06; 95% CI: 1.101-3.873, p = 0.024. No association with age at onset, cognitive impairment or gender was found in our study group. Our data suggest an important role of MTHFR gene variants in SPD.